Prevalence of Rubella Antibodies Among Children in the Democratic Republic of the Congo. Issue 1 (January 2018) - Alfonso, Vivian H.; Doshi, Reena H.; Mukadi, Patrick; Higgins, Stephen G.; Hoff, Nicole A.; Bwaka, Ado; Mwamba, Guillaume Ngoie; Okitolonda, Emile; Muyembe, Jean-Jacques; Gerber, Sue; Rimoin, Anne W.
Abstract : Background: While generally mild in children, rubella infection in early pregnancy can lead to miscarriage, fetal death or congenital rubella syndrome. Rubella vaccination is not yet available as a part of routine immunization in the Democratic Republic of the Congo (DRC), and the burden of infection is unknown. Methods: In collaboration with the 2013–2014 DRC Demographic and Health Survey, a serosurvey was carried out to assess population immunity to vaccine-preventable diseases. Dry blood spot samples collected from children 6–59 months of age were processed using the Dynex Technologies Multiplier FLEX chemiluminescent immunoassay platform (Dynex Technologies, Chantilly, VA). Results: Among the 7195 6- to 59-month-old children, 33% were positive and <1% indeterminate for rubella antibodies in weighted analyses. Seroprevalence was positively associated with age of the child and province, with seropositivity highest in Bandundu (53%) and lowest in Kasai-Oriental (20%). In multivariate analyses, serologic evidence of infection was associated with age of the mother and child, socioeconomic status and geographic location. Conclusions: Rubella infection is prevalent among children in the DRC, and while most seroconversion occurs in young children, a significant proportion of children remain at risk and may enter reproductive age susceptible to rubella infection. While not currently in place, implementation of a surveillance program will provide improved estimates of both rubella virus circulation and the burden of congenital rubella syndrome. Such information will play an important role in future policy decisions, vaccine delivery strategies and may provide a basis upon which the effectiveness of rubella antigen introduction may be assessed.